Riddah (apostasy) efforts in performing interfaith marriages - Afriansyah; Mhd Yadi Harahap (Jurnal Cendikia ISNU SU, 2025)
The phenomenon of riddah or apostasy in the context of interfaith marriage in Indonesia poses significant legal and social complexity. A person's actions to leave religion to marry a follower of another religion raises questions related to the legality of marriage, the status of children, and social implications. Indonesia as a legal country upholds freedom of religion, but Law No. 1 of 1974 concerning Marriage requires religious conformity for couples, so the practice of riddah presents a tension between individual rights and religious norms. This study aims to analyze the efforts of riddah in interfaith marriage normatively, assess the legal, social, and moral consequences, and evaluate the harmonization between national law and fiqh principles. The research focus includes an analysis of the legal status of marriage, children's rights, and social implications for individuals and society. This research also provides normative guidance for law officials, religious leaders, and the community in handling cases of interfaith marriage that trigger riddah. The method used is normative with a descriptive qualitative approach. The analysis was carried out through the study of Islamic legal doctrines, laws and regulations, fatwas of the Indonesian Ulema Council, as well as legal and social literature related to interfaith marriage and apostasy. This approach allows the identification of legal dualism between the absolute norms of Islamic law and positive legal procedures, while assessing the social and moral implications of the phenomenon. The results of the analysis show that riddah for the sake of interfaith marriage causes legal uncertainty and potential for social conflict. Islamic law emphasizes the validity of faith as a valid condition for marriage, while national law requires religious suitability. The normative approach emphasizes the importance of harmonization between positive law, fiqh, and social norms to create legal certainty, moral protection, and social stability. The integration of norms is the main instrument in managing conflicts, guaranteeing individual rights, and maintaining justice in a pluralistic society.